2017
DOI: 10.4103/ijp.ijp_304_16
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction monitoring in patients on antiretroviral therapy in a tertiary care hospital in Eastern India

Abstract: BACKGROUND:Besides unparalleled benefits, highly active antiretroviral therapy is also associated with wide range of potential adverse drug reactions (ADRs), which hinders treatment adherence. The present study was thus designed to monitor and explore the pattern of occurrence of ADRs to various antiretroviral therapy (ART) regimens in a tertiary care ART setup.MATERIALS AND METHODS:A prospective, observational clinical study was carried out in the outpatient setting of nodal ART center of Eastern India. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(15 reference statements)
1
10
1
1
Order By: Relevance
“…Because the study was done in case of antiretroviral medicines where there is no other option but to withdraw the drug when ADR occurs, and continue it upon the alleviation of ADR and so the majority of the ADRs fall under certain or probable causality. 23 Dual drug combinations were prominent in the present study constituting 85 FDCs, and rest were multidrug combinations; similar to the study done by Shende et al 24 Also, 92.23% of FDCs were costlier than the sum of the cost of individual API. This was similar to the study by Nazmi et al stating 70% of FDCs were costlier.…”
Section: Discussionsupporting
confidence: 86%
“…Because the study was done in case of antiretroviral medicines where there is no other option but to withdraw the drug when ADR occurs, and continue it upon the alleviation of ADR and so the majority of the ADRs fall under certain or probable causality. 23 Dual drug combinations were prominent in the present study constituting 85 FDCs, and rest were multidrug combinations; similar to the study done by Shende et al 24 Also, 92.23% of FDCs were costlier than the sum of the cost of individual API. This was similar to the study by Nazmi et al stating 70% of FDCs were costlier.…”
Section: Discussionsupporting
confidence: 86%
“…Tenofovir based regimen was found to be milder with regard to Haematological ADRs compared to Zidovudine based regimens (ZLN /ZLE). 3 Present study has also reported renal adverse events as renal failure, acute kidney injury and nephrotoxicity and also gastrointestinal ADRs. The ADRs due to efavirenz were largely nonspecific with some patients showing raised serum transaminase levels suggestive of hepatotoxicity.…”
Section: Figure 4: Severity Assessment Of Reported Adverse Drug Reactmentioning
confidence: 52%
“…2 Antiretroviral drugs mainly suppress viral load and thus restoring the immune function. 3 In India, NACO has made efforts to make generic HAART available which is very economical due to which many HIV infected individuals are receiving the therapy. 4 Many studies in the developing countries have demonstrated the safety tolerability and efficacy of generic HAART.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The presentation of this treatment in the created nations in the late 90s and the ensuing advancement in giving its availability all around has been related with a striking abatement in AIDS-related mortality, which has changed the standpoint of HIV infection from being a quickly lethal to an incessantly reasonable infection. 2,3 Antiretrovirals mainly suppress viral load, in this way re-establishing the insusceptible capacity. Declining expenses of antiretrovirals alongside the generation of medications by bland producers has helped tertiary care centers in resource limited territories cook better antiretroviral care to HIV-seropositive population.…”
Section: Introductionmentioning
confidence: 99%